The Influence of Financial Management, Risk Perception, and Perceived Investment Return on Stock Investment Decisions among Investors in Pontianak - Dea Sri Rahayu; Dedi Hariyanto; Heni Safitri (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates whether financial management, risk perception, and perceived investment return affect stock investment decisions among 150 individual investors in Pontianak City. Data were collected via structured questionnaires and analyzed using multiple linear regression after passing validity, reliability, and classical assumption tests. The model produced Y = 1.015 + 0.115X1 + 0.221X2 + 0.386X3 with a strong correlation (R = 0.712) and a determination level of R² = 0.507, indicating that 50.7% of the variance in investment decisions is explained by the three predictors. The F-test (p < 0.001) shows a joint significant effect. Partially, all variables have positive and significant effects: financial management (t=2.162; p=0.032), risk perception (t=3.192; p=0.002), and perceived return (t=6.515; p<0.001), with perceived return as the dominant predictor. The findings imply that rational stock decisions are shaped not only by expected profit but also by investors’ capability to manage personal finances and assess risk. Practical recommendations include strengthening financial literacy, emphasizing risk-return trade-off education, and encouraging disciplined portfolio management.